The Wagon, The Phallus and The Conical Hat: Origins and Features of Freyr's Cult in Heathen-Age Iceland - Aðalheiður Eyvör Pálsdóttir 1994- (2017)
This essay aims to examine the features, social demographics and origins of Freyr worship in Heathen-Age Iceland to ascertain to what extent it bears the marks of a Scandinavian Vanir cult, separate from the Icelandic cult of the Æsir (namely, that of Þórr). For this purpose, accounts from saga literature and Landnámabók will be analysed with reference to mythological sources on the Vanir. An attempt will then be made to identify the geographical origins of the Icelandic cult, through analysis of personal names and genealogies.